The Business of Globalization and the Globalization of Business - Passaris, Constantine (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
The new global economy of the twenty-first century has transformed the economic, social, educational and political landscape in a profound and indelible manner. It is composed of a trilogy of interactive forces that include globalization, trade liberalization and the information technology and communications revolution. Globalization has melted national borders, free trade has enhanced economic integration and the information and communications revolution has made geography and time irrelevant. The role and functions of entrepreneurship in the new global economy have taken on added significance and face compounded challenges. We live in a challenging environment of rapidly changing economic events, where the private sector has become the most important engine of economic growth and the public sector has shrunk in importance and influence. Entrepreneurs are defining the new rules of engagement on the economic landscape as they come to grips with contemporary challenges and new opportunities. In this new environment, entrepreneurs need to articulate a pragmatic vision, exercise effective leadership and develop a competent business strategy. They should create the synergies that will allow them to integrate the interactive ingredients of the new economy in order to enhance their competitive advantage. Their business strategy should embrace flexibility, a quick response time and a proactive approach to economic opportunities. This paper will also enumerate the entrepreneurial abilities, skills, competencies and perspectives that are essential pre-requisites for success in the new global economy of the twenty-first century. In short, the economic heartbeat of the new economy is the global entrepreneur with an international mindset.